Body Composition, Physical Activity and VO2max in Untrained Adolescents - Miftah Fathi El Ghina; Muchsin Doewes; Intan Suraya Ellyas (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Decreased physical activity and increased adolescent sedentary lifestyles have become global cardiovascular fitness issues. Unbalanced body composition contributes to low cardiovascular fitness and increases the risk of metabolic disorders. This study aims to analyze the relationship between body composition and physical activity on VO2max in untrained adolescents. This observational analytical study with a cross-sectional design was conducted on untrained adolescents aged 15-18. Body composition was measured using the Xiaomi Body Composition Scale S400. Physical activity levels were measured using the International Physical Activity Questionnaire (IPAQ). VO2max was measured using the Multistage Fitness Test. Physical activity significantly contributed to in untrained adolescents (r=0.675; p=0.000). Total body water had the strongest positive correlation with VO2max (r=0.474;p=0.003), followed by percentage muscle mass (r=0.413;p=0.010) and bone mineral (r=0.401;p=0.013). Body Mass Index (r=-0.418;p=0.009), percentage body fat (r=-0.412;p=0.010), muscle mass (r=-0.403;p=0.012), fat-free mass (r=-0.401;p=0.012) and Basal Metabolic Rate (r=-0.401;p=0.013) showed significant negative correlation with VO2max. Increasing physical activity and improving body composition are key strategies to increase VO2max in adolescents. Interventions involving schools, families, and the community are needed to promote an active lifestyle in this population. The results of this study provide a scientific basis for the development of effective and sustainable fitness programs.